If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+139=x-4
We move all terms to the left:
2x+139-(x-4)=0
We get rid of parentheses
2x-x+4+139=0
We add all the numbers together, and all the variables
x+143=0
We move all terms containing x to the left, all other terms to the right
x=-143
| 4/5=−4c+41 | | 3x-8x-16=0 | | 14h=350 | | 6x+3=45,x=7 | | -075x=2 | | 2(2x-7)=13+3 | | 2*0-y=5 | | x=-7+6x+38-9x | | |-10m-2|=28 | | 1/2x+7=+13 | | -460=t(-20) | | -9x+12=23+13x | | n2+3n-18=0 | | 16x+5=27 | | a/10=-18 | | 32+9w-5=90 | | 4/12y-8/12=10/12 | | n+10=69 | | -7+6x=38-9x | | -10x+14=74 | | 18x+3=33 | | -500=20n | | 4=2.2h=3.7 | | -9x-47=34 | | |10x|=70 | | 17=m-12 | | 10w-6=5w-31 | | -17=7-8w | | 7/8=x28.8 | | 144-x+4=59 | | 15w-10w=5 | | -7.2=-1.2w |